Kejadian Infeksi Cacing Saluran Pencernaan pada Ular Sanca Batik (Phyton Reticulatus) - Tetty Barunawati Siagian; Afrilia Elok Fadila; Hammada Raudlowi (Departement of Mathematics Education, 2023)
The purpose of this study was to identify intestinal worm infections in reticulated pythons (Phyton reticulatus) in captivity. This study used faecal samples of 2 reticulated pythons at the Taru Jurug Animal Park, Solo. Anamnesis of the two pythons found the presence of adult nematode worms in their feces. Examination of adult worms and faeces was carried out macroscopically and microscopically. Microscopic examination of feces using native methods. The results of the examination showed that the adult worms found were Ascaridia galli worms, with characteristics of having a length of 72 mm, yellowish white color, large size, semi-transparent and including nematode worms. Stool examination found ascarid eggs with oval-shaped characteristics with thick albumin. Findings of ascarid worm eggs correlated with findings of adult Ascaridia galli worms. The factor that reticulated pythons in captivity are infected with Ascaridia galli worms is caused by the feed given, namely wild ducks. The Ascaridia galli worm generally infects poultry, such as wild ducks. Ascarid worm eggs that are excreted along with the faeces of the geese can contaminate the cage, feed and drink.